Enhanced Resistance to Pb Poisoning of the Co‐modified Mn/Fe‐pillared Clay Catalysts for NH3‐SCR at Low Temperatures. Issue 10 (7th March 2023) - Wang, Xinpeng; Ye, Qing; Liu, Wenyi; Meng, Fanwei; Yang, Fan; Zhang, Xin; Dai, Hongxing
Abstract: Lead (Pb) is a heavy metal commonly found in industrial exhaust gases, which can reduce catalytic activity of a catalyst for the NH3 ‐SCR reaction. In this study, 4.0 wt% Mn‐loaded Fe‐pillared interlayer clay (4Mn/Fe‐PILC) and its Co‐modified catalyst (2Co‐4Mn/Fe‐PILC) were prepared, in the meanwhile the 4Mn/Fe‐PILC‐Pb and 2Co‐4Mn/Fe‐PILC‐Pb samples were also obtained using the impregnation method with a Pb(CH3 COO)2 aqueous solution. It was found that the addition of 2.0 wt% cobalt could significantly enhance Pb resistance of the 4Mn/Fe‐PILC catalyst. The characterization results revealed that the doping of Co to Mn/Fe‐PILC increased the surface Mn 4+ species concentration, reducibility, and acid site amount, thereby improving Pb resistance of the catalyst. Furthermore, the in situ DRIFTS results demonstrated that Co modification enhanced the adsorption capacity of NH3 or NO, especially influenced formation of the NH3 intermediates and bridging nitrate species, which were also conducive to the improvement in Pb resistance of the catalyst. Abstract : On the basis of Fe‐pillared clay, a Co−Mn/Fe‐PILC catalyst with high NH3 ‐SCR activity and Pb resistance was prepared. Comparing with no Co catalyst, the activity and Pb resistance of catalyst was significantly enhanced after adding Co. The results were further confirmed by DRIFT and other characterization.